Effect of bending process on the fatigue behaviour of high strength steel. (July 2021) - Gothivarekar, S.; Coppieters, S.; Talemi, R.; Debruyne, D.
Abstract: Integrating forming in the fatigue analyses of cold-formed High Strength Steel parts significantly increases predictive accuracy. In this study, the effect of cold-bending is modelled through a coupled forming-fatigue simulation of a bent specimen, made from a 12 mm thick S500MC grade. Different strain hardening models were studied, where a Voce law led to an increase in prestrain of about 10% and a decrease in fatigue life of 20% compared to the reference hardening behaviour. Three bending radii were investigated and a 25% decrease in radius led to a 30% increase in plastic strain. Fatigue tests were performed and a local strain approach resulted in a 76% correspondence with experimental data. Graphical abstract: Unlabelled Image Highlights: A numerical-experimental framework is proposed for the fatigue characterisation of cold-formed high strength steel (HSS). A bent specimen is used for fatigue testing and detailed finite element analysis (FEA). The Smith-Watson-Topper (SWT) criterion is entered in the finite element procedure to visualise the fatigue life.